Pemberdayaan Masyarakat Miskin Melalui Peningkatan Layanan Kesehatan oleh Rumah Sehat BAZNAS Yogyakarta di Desa Wukirsari - Sukendar, Hendrik Basguni (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2018)
In the framework of realizing social welfare as stipulated in the RI Law No. 11 of 2009, where social welfare is a condition of fulfilling the material, spiritual and social needs of citizens in order to live properly and be able to develop themselves, so that they can carry out their social functions. Healthy Home BAZNAS Yogyakarta as one of the institutions engaged in the humanitarian field tries to manifest this condition through improving health services. This study seeks to examine how the empowerment of the poor is carried out by the Yogyakarta RSB in the Wukirsari Village. The research method used is descriptive-qualitative. Data collection techniques use observation, interviews and documentation. In determining the informants the researchers used purposive and snowball techniques. Then the validity of the data uses triangulation techniques. The results of this study suggest that there is a community empowerment strategy carried out by Healthy Home BAZNAS Yogyakarta, among others; health advocacy, establish partnership (partnership) to obtain social support (social support) and implementation of community empowerment in the health sector.